Design of novel flow channels of tubular biomass-syngas fueled SOFC towards uniform temperature distribution. (February 2023) - Wu, Zhen; Zhu, Pengfei; Yao, Jing; Mansor, Mohd Radzi Abu; Chen, Jiechao; Huang, Si-Min
Graphical abstract: Highlights: The effects of three different disturbances on SOFC temperature distribution are compared. The rectangular disturbance works best in reducing temperature gradient. Increasing the number and depth of disturbances can reduce the maximum temperature gradient. The disturbance can also bring side effects about pressure drop and current density reduction. The influence of disturbance on the cell needs comprehensively evaluation. Abstract: The solid oxide fuel cell (SOFC) may suffer structural damage even performance degradation caused by large temperature gradient at high temperature. Therefore, it is necessary to implement thermal management of SOFC to keep temperature gradients within safe limits. In such context, this work designs three novel flow channels and investigates their effects on SOFC temperature distribution characteristics and electrochemical performance. Three novel flow channels with semicircular, rectangular and trapezoidal disturbances are considered. It was found that the temperature gradient and maximum temperature can be decreased to a certain extent by setting the disturbance within the flow channel. Moreover, the rectangular disturbance is better than semicircular disturbance and trapezoidal disturbance in reducing temperature gradient. The maximum temperature and temperature gradient of the cell could be reduced from 880 °C to 840 °C and 24 K/cm to 12 K/cm, respectively by using rectangular disturbance. In the region with a large temperature gradient, increasing the disturbance depth can decrease the temperature gradient more effectively. However, around the region with a small temperature gradient, increasing the disturbance depth results in a large temperature gradient reversely. Moreover, increasing the disturbance depth also reduces the output current density and causes the increase of channel pressure drop. It is suggested to increase the depth of local disturbance where the temperature gradient is large and to reduce the depth of local disturbance where the temperature gradient is already small. By comparison with the decrease of channel thickness, the internal disturbance structure is beneficial to decrease temperature gradient when the air inlet flow rate is kept a constant.